Ideologies of a serial bomber: A longitudinal linguistic appraisal analysis of the writings of the Unabomber - Hunter, Madison (Language and Law / Linguagem e Direito, 2025)
Forensic linguistic and psychological assessments of language evidence each offer useful information about authors, but conclusions reached by one are often considered beyond the scope of the other. This paper explores an interdisciplinary approach intended to help bridge the gap between the two which uses the Appraisal framework as the analytical method but examines the findings through the lens of cognitive psychological theory. The connection between the two disciplines is made through the shared concept of ‘schemas’ – beliefs that impact interpretation of and response to incoming information. More specifically, this study uses the linguistic operationalization of schemas – i.e., something observable through language choices – alongside the cognitive psychological conceptualization – as underlying different psychological traits and symptoms and producing evaluative/perceptual biases. It is argued that the impact of schemas on one’s experience will be reflected in the language one uses to describe and evaluate aspects of that experience. The analysis is conducted on the writings of Ted Kaczynski – the Unabomber – which span almost 30 years and are separated into three time periods: (1) before likely onset of psychiatric symptoms; (2) after onset but before voluntary self-isolation; and (3) just before his first bombing to a few years before his arrest. This dataset affords a unique opportunity to examine not only the potential relationship between language and psychopathology, but also how it may change over time. Results suggest a connection between stance-taking patterns and schemas underlying different psychological traits/symptoms, with some changes over time being observed. While further research is needed, the findings provide evidence in support of an interdisciplinary approach like the one explored here.